Análisis de Modo y Efectos de Falla para identificar Riesgos en el Motor Diésel C4.4 en Remolcadores de 1300 HP (2021)
The following work is aimed at performing the failure mode and effect analysis to identify risks of a team or machine, which is achieved from the implementation and application of the FMEA tool (Analysis of Failure Modes and Effects) being the most used methodology in Reliability Centered Maintenance (RCM), with the which will establish the most appropriate maintenance plan for the mechanical engine Diesel C4.4 used in the 1300 HP tugboats. Taking into account the above, it is possible to improve the availability of the equipment, ensuring the correct operation being carried out in no time determined. Thus, with the implementation of the tool, costs per unexpected outputs of the equipment, while it is possible to identify any type of failure of faster and easier way, thus increasing the probability of having the equipment available up to 80%. It will also be possible to guarantee a preventive and predictive maintenance schedule to reduce the corrective, always in order to know the real needs of the engine or failing that, generate a catalog of failures from it.